Very late arrhythmia recurrences in patients with sinus rhythm within the first year after catheter ablation: The Leipzig Heart Center AF Ablation Registry. Issue 11 (22nd August 2019) - Kornej, Jelena; Schumacher, Katja; Sommer, Philipp; Potpara, Tatjana; Arya, Arash; Dagres, Nikolaos; Bollmann, Andreas; Husser-Bollmann, Daniela; Lip, Gregory Y H; Hindricks, Gerhard
Abstract: Aims : Arrhythmia recurrences after catheter ablation of atrial fibrillation (AF) still remain an important management issue. Recently, the APPLE score had been introduced to predict rhythm outcomes within 12 months after catheter ablation, while the simple MB-LATER score was developed for the prediction of very late recurrence of AF (VLRAF) occurring after 12 months. The aim of this study was to compare APPLE and MB-LATER scores in predicting VLRAF. Methods and results : The study population included arrhythmia-free patients within first 12 months after first radiofrequency catheter ablation from The Heart Center Leipzig AF Ablation Registry. The APPLE [one point for A ge >65 years, P ersistent AF, im P aired eGFR <60 mL/min/1.73 m 2, Left atrial (LA) diameter ≥43 mm, E F <50%] and MB-LATER scores [one point for M ale gender, B undle branch block or QRS >120 ms, L A diameter ≥47 mm, A F T ype (persistent AF), E arly R ecurrence <3 months] were calculated before and 3 months after ablation, respectively. We followed 482 patients age 61 [interquartile range (IQR) 54–68] years, 66% males, 32% persistent AF for median 40 (IQR 35–50) months. There were 184 patients (38.3%) with arrhythmia recurrences within 13–60 months after ablation. On multivariate analysis, APPLE [odds ratio (OR) 1.517, 95% confidence interval (CI) 1.244–1.850, P < 0.001] and MB-LATER (OR 1.437, 95% CI 1.211–1.705, P < 0.001) scores and diabetes mellitus (OR 2.214, 95% CI 1.353–3.625, P = 0.002) were significantly associated with arrhythmia recurrences. Receiver operating characteristic curve analyses demonstrated moderate prediction for both scores [area under the curve (AUC) 0.607, P < 0.001 for APPLE score, AUC 0.604, P < 0.001 for MB-LATER]. Conclusion : Prediction of VLRAF is similar for both APPLE and MB-LATER scores. A better score remains still a clinical unmet need.